PWE-279 The hepatic effects of a high fructose vs a high glucose diet in healthy overweight men. (28th May 2012) - Johnston, R D; Stephenson, M C; Crossland, H; Cordon, S M; Taylor, M A; Aithal, G P; Macdonald, I A
Abstract : Introduction: A high intake of fructose has been implicated in NAFLD aetiology. As the majority of dietary fructose originates from sucrose it remains uncertain if these observations are fructose-specific. Infrequent and inconsistent differences in hepatic metabolism have been shown with a high intake of fructose or glucose, the constituents of sucrose. 1 2 There is no prior comparative data in healthy overweight men, and none in the isoenergetic state. Methods: 32 healthy, centrally overweight males were randomised to two periods each of 2 weeks of either a high fructose or glucose intake in a non-crossover fashion. Isoenergetic status was maintained by providing foodstuffs during the first period, followed by a 6-week washout and then a second period of ad libitum overfeeding. The sugars contributed 25% of predicted total energy requirements, and were consumed 4 times a day dissolved in water. The primary outcome was hepatic triglyceride content ( 1 H MRS), with further assessments of calf lipid ( 1 H MRS), deuterated glucose hyperinsulinaemic euglycaemic clamps, and indirect calorimetry. Outcomes assessed by Student t test. Results: The groups were well matched at study entry. Overall the subjects' mean age was 34 years, BMI 29.4 kg/m 2 and daily dose of sugars was 217 g. The changes in the primary measures are shown in the Abstract PWE-279 table 1 below. There were no changes during the energy balanced period. With energy and monosaccharide overfeeding weight, serum triglycerides, liver lipid and biochemistry increased significantly, but to a similar extent in both groups. Further to this the groups did not differ in terms of satiety, whole body oxidative profile, hepatic insulin resistance, calf lipid, or renal function. Conclusion: There were no differences between a high fructose and glucose diet in relation to hepatic lipids or biochemistry. The changes during the overfeeding period were strongly associated with changes in weight, reinforcing the interpretation that these were an energy, as opposed to a nutrient, specific effect. Clinical trial registration number: NCT01050140. Competing interests: None declared. References: 1. Stanhope KL, Schwarz JM, Keim NL, et al. Consuming fructose-sweetened, not glucose-sweetened, beverages increases visceral adiposity and lipids and decreases insulin sensitivity in overweight/obese humans. J Clin Invest 2009;119 :1322–34. 2. Ngo Sock ET, Lê KA, Ith M, et al. Effects of a short-term overfeeding with fructose or glucose in healthy young males. Br J Nutr 2010;103 :939–43.